Influence of Temperature and Ionic Strength of Medium on Surface Potential of Human Erythrocytes - Gordiyenko, Olga I.; Kovalenko, Igor F. (Problems of Cryobiology and Cryomedicine, 2017)
During freezing of cell suspensions the ionic strength of extracellular and, subsequently, intracellular media is responsible for the changes in membrane potential of cells. In this research we revealed the temperature and concentration dependencies of the surface potential of human erythrocytes during freezing of the cell suspension at the points corresponding to the values of temperature and 1:1 concentration of the electrolyte according to the phase diagram of a water-NaCl binary system. The concentrations of sodium ions on the surface of erythrocytes depending on concentration and temperature of the bulk solution were determined. It has been shown that the concentration of sodium ions on the surface of cells was 1.5 times higher than that in the bulk solution. The kink of surface potential temperature dependence for human erythrocytes for 0.15 and 0.3 M concentrations of 1:1 electrolyte within 8...12°C temperature range was of special interest. This temperature dependence feature of the surface potential calculated for the charged surface with a particular surface charge density from the purely physical considerations without taking into account the structure and composition of the surface could be one of the causes of rearrangements in membrane at these temperatures. Misbalance of electrostatic interactions on the surface of membrane outer monolayer appeared as a result of an increased concentration of counterions on the surface of cells and correspondingly the reduced surface potential might trigger the rearrangements and changes in relationships between membrane protein and lipid components. Probl Cryobiol Cryomed 2017; 27(1): 19–28